Implementasi INVOPER (Inovasi Pertanian) dengan Sistem Aquaponik sebagai Teknologi Tepat Guna dalam Budidaya Lele - Naflah Azmi Nur Aisyah; Anjelina Sugianti; Habib Zainal Muhtarom; Daniel Putra Prastyawan; Muhammad Thoriq Ardiazza (Lembaga Pengembangan Kinerja Dosen, 2023)
Technological developments, especially in agriculture, must develop because of the increase in population and climate change requires us to look for innovative sustainable solutions in agriculture because agriculture is a very basic field in human life. Therefore, our group which is a group of students who carry out service in Penjaringansari village made an agricultural innovation with an appropriate technology aquaponics system in catfish cultivation as one of its work programs.This service is carried out by the method of active participation approach of partner groups that is tailored to the needs of the community by our group. The initial stage carried out is catfish cultivation then combines with a hydroponic system in plants to form an aquaponics system. The treatment process is carried out by checking thoroughly regularly.This service program is expected to provide benefits for the people of Penjaringansari Village and can be implemented properly after the completion of KKN. This program aims to improve food security and community independence through limited land use in the yard.